Bimaadiziwin, or the “Good Life,” as a Unifying Concept of Anishinaabe Religion - Gross, Lawrence W. (eScholarship, University of California, 2002)
The experience of the Anishinaabe in the modern world contains a great amount of variety, from those who are fluent in their language and culture to those who, in the aftermath of the boarding school experience and similar assaults on Native cultures, are “in recovery.” I belong to the latter group. My mother attended boarding schools during the 1930s and 1940s, and “relocated” to Minneapolis in the early 1950s. After moving to a small town in central Minnesota with my father, she raised nine children. Being the only children of Indian descent in school, there were times when our Indian identity was painfully obvious. Yet, as a whole, the exact contours of Anishinaabe culture remained elusive to us simply because our mother was not in a position to provide much information, and there was not an Indian community in town to support us. Much of my adult life, then, has involved a process of recovering my Anishinaabe identity, although I will be the first to admit I have a long way to go in that regard. One part of the search led me to Thomas Shingobe, a respected spiritual leader of the Anishinaabe community in Minneapolis, Minnesota, in the 1970s. As part of our conversations, Shingobe would often mention the “Proper Conduct of Life,” although he never explained the term, and I never asked. It was not until years after he died that I realized he was trying to convey something of importance to me. It was with renewed conviction, then, that I set about to understand what I believe Shingobe was talking about: bimaadiziwin, or the “good life,” as defined by the Anishinaabe. The following are my preliminary thoughts on the subject as I continue to pursue the good life of the Anishinaabe. The moral structure of traditional Anishinaabe religion as encapsulated by the term bimaadiziwin is at least one unifying concept providing continuity in the worldview of the Anishinaabe from the past into the modern era. Bimaadiziwin, or the Good Life, can basically be described as a long and healthy life, and was the life goal for ...